The Influence of HEV-Filtering Contact Lenses on Behavioral Indices of Glare. Issue 12 (6th December 2022) - Renzi-Hammond, Lisa M.; Buch, John; Xu, Jie; Hammond, Billy R.
Abstract : Objectives: We assessed the effects of a HEV-filtering contact lens on positive dysphotopsia (halos and starbursts) and a behavioral index of scatter measured using two-point light thresholds. These effects were assessed by direct comparison to a clear (i.e., non-HEV filtering) contact lens tested in the fellow eye. Methods: Sixty-one subjects were randomized and fit with study lenses and 58 subjects completed the study. A double-masked contralateral design was used. Subjects were randomized to test lens-OD, control lens-OS, or vice versa. Participants were exposed to a point source of broadband simulated sunlight (a 403-nm condition was also tested) that created the appearance of halos/starbursts. The degree of dysphotopsia was measured as the diameter of broadband and violet-induced halos, and broadband light-induced starbursts. Two-point thresholds were assessed as the minimum resolvable distance between two pinpoints of light. Results: The HEV-filtering lens was statistically superior ( P <0.0001) to the clear lens in all the conditions tested. The HEV-filtering lens significantly reduced halo diameter by 30%, starburst diameter by 23%, and resolvable distance in the two-point condition by 18% (white) and 30% (violet). Conclusions: HEV-filtering contact lenses can reduce some deleterious effects of bright broadband light by decreasing light scatter, halos, and starbursts.